1998
DOI: 10.1002/ctpp.2150380149
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Neutral Gas Models for Divertor Plasmas

Abstract: DISCLAIMER

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…We believe that providing more overlap information in the preconditioner may allow this problem to be overcome, such as using a Schur complement method [12,20] or other other schemes [10]. Also, when using a Monte Carlo neutrals code for the gas description [21], this problem goes away, and one gets the added benefit that Monte Carlo codes parallelize very well. On the other hand, one must then achieve convergence of the separate plasma and neutral descriptions by an iteration procedure [22].…”
Section: Discussionmentioning
confidence: 98%
“…We believe that providing more overlap information in the preconditioner may allow this problem to be overcome, such as using a Schur complement method [12,20] or other other schemes [10]. Also, when using a Monte Carlo neutrals code for the gas description [21], this problem goes away, and one gets the added benefit that Monte Carlo codes parallelize very well. On the other hand, one must then achieve convergence of the separate plasma and neutral descriptions by an iteration procedure [22].…”
Section: Discussionmentioning
confidence: 98%
“…Monte Carlo treatment of neutrals can be regarded as a necessity whenever long neutral trajectories exist (e.g., in regions of low plasma density). A comparison of fluid and Monte Carlo neutral transport codes in slab geometry has shown that the power at which the transition between attached and detached divertor plasma occurs agrees to within 30% in these models [10]. It should be noted that the simulations require the determination of several input parameters that are not well known experimentally, such as the anomalous transport coefficients at the plasma edge, the effective pumping rate of the plasma facing components, and the fraction of the target ion current that recycles as neutrals.…”
Section: Introductionmentioning
confidence: 87%
“…A comparison of fluid and Monte Carlo neutral transport codes in slab geometry has shown that the power at which the transition between attached and detached divertor plasma occurs agrees to within 30% in these models [10]. A comparison of fluid and Monte Carlo neutral transport codes in slab geometry has shown that the power at which the transition between attached and detached divertor plasma occurs agrees to within 30% in these models [10].…”
Section: Introductionmentioning
confidence: 92%
“…[35]. Finally, the expression κ n " χ n p n D pn is used for the neutral conductivity, while transverse plasma conductivity and ion viscosity are respectively given by κ r " nD κ and η r " mn i D r i .…”
Section: Plasma Edge Transport Simulationmentioning
confidence: 99%